Effect of tea polyphenols supplement on growth performance, antioxidation, and gut microbiota in squabs - Chen, Ailing; Ma, Tingting; Zhong, Yajing; Deng, Shan; Zhu, Shaoping; Fu, Zhiqi; Huang, Yanhua; Fu, Jing (Frontiers in Microbiology, 2024)
Early-life nutritional supplementation can significantly improve pigeon health. Both the nutritional crops of parental pigeons and the intestinal development of squabs play key roles in the growth rate of squabs. Tea polyphenols (TPs), as natural plant extracts, exhibit potential biological activities. However, the impact of TPs on the intestinal function of squabs is not known. This study evaluated the effects of TPs on growth performance, immunity, antioxidation, and intestinal function in squabs. A total of 432 young pigeons (1 day old) were divided into four groups: a control group (fed a basic diet) and three treatment groups (low, medium, and high dose groups; 100, 200, and 400 mg/kg TPs, respectively). On the 28th day, samples of serum, mucosal tissue, and digests from the ileum of squabs were collected for analysis. The results revealed that TP supplementation significantly reduced the feed-to-meat ratio and improved the feed utilization rate and serum biochemical indices in squabs. Additionally, it enhanced the intestinal barrier function of birds by promoting intestinal development and integrity of tight junctions and regulating digestive enzyme activities and intestinal flora. Mechanistically, TPs activated the Nrf2-ARE signaling pathway, which may be associated with improved antioxidant and immune responses, correlating with an increased abundance of Candida arthritis and Corynebacterium in the ileum.